2022
DOI: 10.1088/2515-7655/ac5f37
|View full text |Cite
|
Sign up to set email alerts
|

Electronic scattering in half-Heusler thermoelectrics from resistivity data

Abstract: A key part of optimising thermoelectric materials is understanding the electronic scattering mechanism. For half-Heusler thermoelectrics, the dominant mechanisms are acoustic phonon scattering in pure systems and alloy scattering in highly alloyed systems. In this report, the significance of the residual resistivity ρ0 is highlighted. Large ρ0 values can lead to misidentification of the dominant scattering mechanism when only high-temperature ρ(T) data is available. A straightforward approach to analyse ρ(T) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Analysis of transport data has suggested that there is metal-like electronic conduction through the impurity band in addition to the regular valence and conduction bands . In order to accommodate these two conduction channels, σ( T ) was fitted using a parallel degenerate (σ deg , metal-like) and semiconducting (σ int ) channel σ = σ deg + σ int = ( ρ 0 + A T 1.5 ) 1 + B e false( prefix− E g / 2 k normalB T false) Here, the T 1.5 temperature dependence is typical for acoustic phonon scattering and ρ 0 is the residual electrical resistivity at 0 K. The intrinsic term does not explicitly consider the high mobility ratio, but this minimal model provides a good fit to the data. The final fit parameters are given in Table , and the quality of the fit can be inspected in Figure a.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of transport data has suggested that there is metal-like electronic conduction through the impurity band in addition to the regular valence and conduction bands . In order to accommodate these two conduction channels, σ( T ) was fitted using a parallel degenerate (σ deg , metal-like) and semiconducting (σ int ) channel σ = σ deg + σ int = ( ρ 0 + A T 1.5 ) 1 + B e false( prefix− E g / 2 k normalB T false) Here, the T 1.5 temperature dependence is typical for acoustic phonon scattering and ρ 0 is the residual electrical resistivity at 0 K. The intrinsic term does not explicitly consider the high mobility ratio, but this minimal model provides a good fit to the data. The final fit parameters are given in Table , and the quality of the fit can be inspected in Figure a.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of transport data has suggested that there is metallike electronic conduction through the impurity band in addition to the regular valence and conduction bands. 58 In order to accommodate these two conduction channels, σ(T) was fitted using a parallel degenerate (σ deg , metal-like) and semiconducting (σ int ) channel 62 AT Be ( )…”
Section: Methodsmentioning
confidence: 99%
“…At this point it is unclear if acoustic phonon scattering is indeed the dominant scattering mechanism, with optical phonon and ionised impurity scattering also likely to contribute, but the obtained values of E def are fairly large for thermoelectric materials. 28,[127][128][129] Further work on understanding electronic transport (carrier scattering) in these materials is needed and can provide avenues for further materials discovery and optimisation.…”
Section: Discussionmentioning
confidence: 99%
“…There continues to be a need for improved thermoelectric materials, based on sustainable large power factors (S 2 σ) but their overall zT continues to be limited by large intrinsic thermal conductivity. 27,28 There is considerable interest in Zintl thermoelectrics based on Sb, with antimonide skutterudites reported with large S 2 σ and zT [29][30][31][32][33] and more recently Mg 3 Sb 2 phases with high zT near room temperature in n-type samples. [34][35][36][37][38] There are several excellent reviews and book chapters covering Sb-based thermoelectrics, [39][40][41][42][43][44] which support very good zT values, often substantially exceeding unity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation